Emergence of Synthetic Cannabinoids as Drugs of Abuse - Nupur Joshi; Mahipal Singh Sankhla (Institute of Medico-legal Publications Pvt Ltd, 2022)
Cannabis has been the most commonly used drug throughout the world for centuries. The psychoactiveproperties of cannabis are largely attributed to Δ9-tetrahydrocannabinol or THC, the active psychoactiveingredient in the cannabis plant. Lately, new psychoactive substances (NPS) have appeared that aremostly ruled by cathinone’s and synthetic cannabinoids (SCs). SC’s have emerged as drugs of abusebecause of their ability to mimic the euphoric effects of THC. Sprayed on natural herb mixtures, theywere initially sold as ‘herbal incense’ or ‘herbal smoking blends’ as substitutes for cannabis. Thesesynthetic drugs became popular as ‘legal highs’ under brand names such as Spice, K2, Mojo and manyothers in the early 2000’s. SC’s stimulate the same CB1 and CB2 receptors as THC but they are linkedto higher toxicity in terms of duration and severity than cannabis. This is because SC’s act as directagonist of cannabinoid receptors, whereas THC being a partial agonist. Reports suggest that SC’s areassociated with a range of undesired pulmonary, cardiovascular, gastrointestinal effects. Long term SCuse is also linked to severe cognitive deficits. With the global rise in use of SC products, it is importantto develop and validate the screening procedures and investigate the toxicological and pharmacologicalaspects and risk factors associated with its use and abuse.